2016
DOI: 10.1080/08039488.2016.1204469
|View full text |Cite
|
Sign up to set email alerts
|

Processing speed is associated with differences in IQ and cognitive profiles between patients with schizophrenia and their healthy siblings

Abstract: Significant differences in cognitive speed between patients and their healthy siblings generate the differences in the cognitive profile assessed with Wechsler Intelligence Scale. Some problems of cognitive speed diagnosis and further research on the cognitive schizophrenia endophenotype were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…To date, two to five cognitive trajectories have been identified in patients with psychosis who differ in terms of demographic and clinical characteristics . Cognitive alteration is also common in unaffected siblings, but to a lesser extent, and subtyping is relevant to identify meaningful homogeneous trajectories . In our previous cross‐sectional study, we demonstrated three subtypes of cognitive alteration (i.e., normal, mixed, and impaired) in siblings .…”
Section: Introductionmentioning
confidence: 79%
“…To date, two to five cognitive trajectories have been identified in patients with psychosis who differ in terms of demographic and clinical characteristics . Cognitive alteration is also common in unaffected siblings, but to a lesser extent, and subtyping is relevant to identify meaningful homogeneous trajectories . In our previous cross‐sectional study, we demonstrated three subtypes of cognitive alteration (i.e., normal, mixed, and impaired) in siblings .…”
Section: Introductionmentioning
confidence: 79%
“…Cognitive impairment in schizophrenia can be selective or general though the most common deficits occur in executive function, processing speed, memory (e.g. episodic, verbal and working), attention, verbal fluency, problem-solving and social cognition [8][9][10][11] . Patients harbor a wide range of subjectively defined symptoms, which together yields instinctively heterogeneous groups of people who are collectively diagnosed with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…We chose these two cognitive dimensions for two reasons: earlier studies demonstrated that impaired processing speed significantly contributes to differences between patients, their siblings and healthy individuals regarding any other cognitive dimensions 3739 . Because cognitive speed in SZ patients is related to white matter integrity 40,41 and strength of long-range synchronization 42 , we assumed that its disruption should be associated with global network properties, such as centrality or assortativity.…”
Section: Introductionmentioning
confidence: 99%